The early drug courts case studies in judicial innovation - Terry, W. Clinton; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1998)
This volume presents five case studies in judicial innovation - the dedicated drug treatment courts in Miami, Oakland, Fort Lauderdale and Phoenix. It will be of interest to academics and students in criminal justice, law, social work and health.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Drug courts -- United States; Drug abuse -- Treatment -- Law and legislation -- United States; Electronic books